The Frequency of Rotavirus Infection among Children under the age 5 years in Erbil Province, Kurdistan Region, Iraq, a hospital based study - Dawod Nasih, Lana; Sabir Ali , Katan (Diyala Journal of Medicine, 2023)
Background:Globally, rotavirus infection, which results in gastroenteritis, is one of the major health problems. Millions of children are infected with the disease. Viral gastroenteritis must be recognized early because it causes wasteful antibiotic use and hospitalizations for kids. Objective: To investigate the frequency of rotavirus in stool samples from children with acute gastroenteritis. Patients and Methods: Cross-sectional study consisting of one hundred fifty-three fresh stool samples collected from children less than 5 years were admitted to Raparin pediatric hospital in Erbil city between November 2021 and April 2022. Rotavirus antigens were detected by Rapid test. Results: Rotavirus antigen was detected at an estimated rate of 61 (40%) in 153 studied cases. The frequency of rotavirus among male and female patients was 44.1% and 33.3% respectively. According to age of infants, rotavirus was detected most frequency in eight months of age. As well as the frequency rate among rural and urban patients was 40% and 39.8% respectively. Rotavirus was detected among vaccinated and non-vaccinated patients by the frequency 26.3% and 54.8% respectively. The highest frequency rate was detected in January 46.4%. Detection of rotavirus by age group was and vaccinations were significant in this study by p-value of 0.001. Conclusion: The most common cause of acute gastroenteritis in children in our area is rotavirus . Rotavirus infection is most frequently occurring during the winter season and among children between 6 months to 24 months. Conclusion: In this study we found cigarette smoking was more commonly practiced than water pipe .Nicotinic stomatitis is more prevalent in cigarette smoking and its incidence increased with duration and frequency of the habit.